Evolution in health and disease - Stearns, S. C. (Stephen C.); Koella, Jacob C. (Oxford University Press, 2008)
It is now increasingly acknowledged that an evolutionary perspective can give us important new insights into issues central to medical research and practice. This fully revised and updated edition, which consists of roughly 95% new material, contains contributions from leading researchers who provide a fresh summary of this rapidly expanding field. It takes a broad approach to the subject, discussing medically relevant research from evolutionary genetics, evolutionary ecology, evolutionary epidemiology, the evolution of aging, and any other biological disciplines where evolutionary approaches make important contributions. The medical conditions discussed include diabetes, obesity, cardiovascular disease, asthma, allergies and other autoimmune diseases, infectious diseases, emerging diseases, and aging. It also provides insights into the evolutionary responses of pathogens to antibiotics and vaccines. What will happen if we continue to expand our use of antibiotics and vaccines? Why do we respond inappropriately (for example by developing cardiovascular disease) to many modern conditions? How do cancers evolve, particularly in response to chemotherapy? Why must we grow old, and can we do anything about it? This book discusses answers to these and many other questions.